The Effect of Globalization on National Income Inequality - Bussmann, Margit; De Soysa, Indra; Oneal, John R. (My University, 2005)
We assess the effect of globalization on income inequality within countries, focusing on the influence of accumulated foreign direct investment stocks. We analyze data on inequality and foreign investment for 72 countries, 1970-90, incorporating in our tests the Kuznets (1955) curve, the character of political institutions, and various other aspects of the economy and society emphasized in previous research. Our results indicate that globalization does not increase national income inequality. The ratio of foreign direct investment to gross domestic product is unrelated to the distribution of incomes in both developing and developed countries. The share of income received by the poorest 20% of society also is unaffected by foreign investment. Nor are alternative measures of economic openness the trade-to-GDP ratio and Sachs and Warner s (1995) measure of free trading policies associated with greater income inequality. If foreign investment increases average incomes in developing countries, as recent research indicates, and does not increase inequality, it must benefit all strata of these societies, including the poor.
Keywords: Globalization; 320